ҚАРАҚАЛПАҚ, АНГЛИЧАН ХАЛЫҚЛАРЫ ЕРТЕКЛЕРИ. ЕРТЕКШИЛЕРДИҢ ТУТҚАН ОРНЫ, АТҚАРЫЎШЫЛЫҚ ШЕБЕРЛИГИ - Сайтова, З.К. (ILIM hám JÁMIYET, 2022)
Fairy tales are usually invented and told by one person and then become folk art. These folklore works have different variants, and as the form of the work changes, the content becomes more popular while being preserved. The place of folk tales and storytellers, the ability to perform them is important. In addition, each storyteller have his own style. Some tell magical, fantastic tales, while others tell more everyday tales. Their use of artistic means of expression is also not the same. The study of the style and characteristics of storytellers is one of the urgent problems of folklorists.